2017
DOI: 10.3390/molecules22111930
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cellulose Triacetate as Support for Lecitase Ultra Immobilization

Abstract: The use of polymers as supports for enzyme immobilization is a strategy that enables to remove the enzymes from a chemical reaction and improve their efficiency in catalytic processes. In this work, cellulose triacetate (CTA) was used for physical adsorption of phospholipase Lecitase ultra (LU). CTA is more hydrophobic than cellulose, shows good performance in the lipases immobilization being a good candidate for immobilization of phospholipases. We investigated the immobilization of LU in CTA, the stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…CTA presents a great balance of the hydrophilic/hydrophobic character important for effective enzyme adsorption and its biological activity. Additionally, hydrophilic/hydrophobic properties could be modified by acetylation/deacetylation [ 69 ]. Both strains were able to degrade 2 mg/L of estrone and 17β-estradiol for free strains in 24 h and for immobilized in 72 h, which is probably caused by the compounds transfer limitation in a porous carrier.…”
Section: Immobilized Systems In Microbiological Degradation Of Edcmentioning
confidence: 99%
See 1 more Smart Citation
“…CTA presents a great balance of the hydrophilic/hydrophobic character important for effective enzyme adsorption and its biological activity. Additionally, hydrophilic/hydrophobic properties could be modified by acetylation/deacetylation [ 69 ]. Both strains were able to degrade 2 mg/L of estrone and 17β-estradiol for free strains in 24 h and for immobilized in 72 h, which is probably caused by the compounds transfer limitation in a porous carrier.…”
Section: Immobilized Systems In Microbiological Degradation Of Edcmentioning
confidence: 99%
“…Both strains were able to degrade 2 mg/L of estrone and 17β-estradiol for free strains in 24 h and for immobilized in 72 h, which is probably caused by the compounds transfer limitation in a porous carrier. Additionally, the authors reported that a continuous-flow degradation on an IBRC reactor of 850 ng/L 17β-estradiol is possible [ 69 ].…”
Section: Immobilized Systems In Microbiological Degradation Of Edcmentioning
confidence: 99%
“…However, in many cases, it is also related with a decrease in enzyme activity caused by various types of distortion, diffusion, and steric problems [46]. As Lecitase™ Ultra is commercially available only in its free form as the water solution, many attempts have been made to prepare an immobilized form of this enzyme for different purposes, for example, by entrapment in gelatin hydrogel [47] or in different calcium alginates [48], immobilization on the derivatives of cellulose [49,50], polystyrene resin [51], styrene-divinylbenzene beads [37,52], magnetic nanoparticles [53], or by encapsulation in AOT(bis(2-ethylhexyl) sulfosuccinate sodium salt)/isooctane reverse micelles [54]. In the processes of the kinetic resolution of racemates catalyzed by immobilized Lecitase™ Ultra, the best results were obtained using gelatin [35,39], various derivatives of agarose [33,36,38,41,55], hexyl-and butyl-toyopearl [34], or epoxy activated polymer Dilbead VWR coated with polyethylenimine (PEI) and crosslinked with glutaraldehyde [40].…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization of enzymes by adsorption is one of the oldest and also the most frequently used methods due to the relatively low costs and simple procedure. LU adsorbed physically on cellulose triacetate was used for the production of fatty acid methyl esters from soybean oil by transesterification [43]. Adsorption of LU on different ionic and macropourous resins found applications in lipid chemistry, including acidolysis of phospholipids [28,44,45], glycerolysis of soybean oil [46], esterification of glycerol with oleic acid [47], hydrolysis of phosphatidylcholine to lysophosphatidylcholine [48], and esterification of isopropylidene glycerol in the production of monoacylglycerols [49].…”
Section: Introductionmentioning
confidence: 99%